2003
DOI: 10.1046/j.1365-2125.2003.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of liposomal daunorubicin in children

Abstract: AimsTo investigate the population pharmacokinetics of daunorubicin in children after administration of liposomal daunorubicin (Daunoxome ® ). Methods Plasma samples from 19 children with relapsed acute myeloic leukaemia and five children with other malignancies were collected. Daunoxome ® was administered as a 1-to 2.5 h infusion with doses ranging from 30 to 60 mg m -2 . Overall, 214 samples were analysed for daunorubicin using capillary electrophoresis, and population pharmacokinetic modelling was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…23 Low accumulation of L-DNR in the heart has been proven in animals, and minimal cardiotoxicity despite significant antileukemic activity was found in a mouse model. 8,9 In 277 AIDS patients with Kaposi sarcoma, no cardiotoxicity of L-DNR was seen, after cumulative doses of up to 1700 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Low accumulation of L-DNR in the heart has been proven in animals, and minimal cardiotoxicity despite significant antileukemic activity was found in a mouse model. 8,9 In 277 AIDS patients with Kaposi sarcoma, no cardiotoxicity of L-DNR was seen, after cumulative doses of up to 1700 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The high PK variability of LAMB may be founded in differences in the uptake of the liposomal carrier with bound drug into nonblood compartments or in the dissolution of the drug from the liposomal carriers with consequences for its disposition in the blood; further potential factors include differences in disease status and inflammatory molecules, the composition of plasma proteins, and solutions used for concomitant parenteral nutrition (3). Interestingly, liposomal encapsulation of daunorubicin with liposomes of similar structure (Daunoxome) resulted in a substantial reduction of IIV in the PK parameters (17).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first paediatric study with liposomal Daunorubicin that has shown a significant degree of cardiac toxicity, albeit with repeated dosing. Three other paediatric studies have been performed, but none of these raised concerns over the degree of cardiac toxicity (Baruchel, personal communication;Lippens, 1999;Hempel et al, 2003). The treatment regimes used in these studies differ significantly from the present study: in both, patients were given four doses over a 4-week time period.…”
Section: Discussionmentioning
confidence: 75%